2010
DOI: 10.1111/j.1439-0434.2010.01674.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-temporal Analysis of Gummosis in Three Cashew Clones at Northeastern Brazil

Abstract: The cashew gummosis caused by the fungus Lasiodiplodia theobromae is one of the most important disease of cashew in the northeast of Brazil. The lack of studies about method of early detection, pathogen dissemination, host predisposition, mechanisms of attack and defence and efficient control measures assures this disease as a limiting factor as to growing of cashew under semi-arid conditions. Therefore, the characterization of spatial patterns of gummosis development under commercial orchards may provide impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
(41 reference statements)
1
8
0
Order By: Relevance
“…Our results are consistent with those of Freire et al [10] and Araújo [4]. Some studies revealed that fungi are responsible of gummosis [6].According to this author, up to now, despite the important damage induced by gummosis disease on cashew, no efficient measure is available to control it. Many authors reported an increase in gummosis severity in all north-eastern producing states in Brazil [6-7-17].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent with those of Freire et al [10] and Araújo [4]. Some studies revealed that fungi are responsible of gummosis [6].According to this author, up to now, despite the important damage induced by gummosis disease on cashew, no efficient measure is available to control it. Many authors reported an increase in gummosis severity in all north-eastern producing states in Brazil [6-7-17].…”
Section: Discussionsupporting
confidence: 92%
“…Unfortunately, cashew is threatened by many biotic and abiotic constraints resulting in significant yield losses. Among biotic constraints, diseases and pests are the most damaging and compromise the cashew nut yield in terms of quality and quantity [4][5][6][7][8][9][10][11][12][13][14][15]. Indeed, more than 12 diseases were reported to infect cashew tree worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Gummosis, which is a common response to pathogen infection, wounding or insect attack, is the process of gum accumulation and exudation in some plant species, such as tulip, grape hyacinth, cashew and the stone fruit tree species of Rosaceae (Saniewski et al ., ; Cysne et al ., ; Miyamoto et al ., ). Peach gummosis, caused by Botryosphaeria spp.…”
Section: Introductionmentioning
confidence: 98%
“…Samples were collected in Pio IX county (state of Piauí, Brazil) from the branches and leaves of naturally infected cashew plants of the commercial clone CCP‐76. This cashew orchard has been studied and proven to be infested by L. theobromae (Cysne et al ., ), and infected plants exhibited different severities of gummosis. Plants with no symptoms were also collected.…”
Section: Methodsmentioning
confidence: 99%